A tribo Cymbidieae (Orchidaceae) no estado do Ceará, Brasil - Farias, Diego Costa (2024)
Cymbidieae Pfitzer belongs to the Orchidaceae family and is positioned within the subfamily Epidendroideae. It is one of the largest clades within Orchidaceae, comprising 10 subtribes with 3,998 species, predominantly distributed in the tropical region of the Americas. They are characterized as epiphytic herbs, rarely terrestrial, usually with pseudobulbs, pleated or folded leaves, jointed, basal inflorescences, sometimes fused lateral sepals, free petals, and generally trilobed labellum. Despite the significant representation of the Orchidaceae family in Ceará (41 genera and 83 species), there are no taxonomic works addressing its representatives in the state. Therefore, this study aimed to understand the Cymbidieae tribe in the state of Ceará, based on morphological, biogeographic, and conservation data, contributing to the knowledge of the Orchidaceae family in the state. Collections deposited in the herbaria EAC, EAN, HCF, HEPH, HUEFS, HRSN, IPA, NHM, NY, R, SP, UEC, UFMT, and UFP, available on the Centro de Referência de Informação Ambiental – CRIA and Flora e Funga do Brasil websites, originating from individuals in natural populations of various vegetation formations in the state, collected during field expeditions, were used for this purpose. For the morphological study, identifications were made with the aid of specialized bibliographies and confirmed by analyzing the type collections. For biogeographic and conservation studies, a geographic coordinates database of species occurrences was created, from which maps were developed with assessments of richness, diversity, similarity analyses, and PAE. The research identified 13 genera and 27 species of the Cymbidieae tribe in the state of Ceará. Maxillaria was the most representative genus with six species, followed by Catasetum (5), Cyrtopodium (3), Gomesa (2), Notylia (2), and Trichocentrum (2), Dichaea, Gongora, Leochilus, Ornithocephalus, Rodriguezia, and Trizeuxis each presented one species. The study presents six new records for Ceará. The species mostly inhabit in the Dense Ombrophilous Forest associated with high- altitude marshes. The region with the highest richness and species diversity encompasses the Baturité massif area in the northeastern part of the state. The Maranguape massif in the metropolitan region is a secondary center of richness and diversity. The results of similarity analyses and PAE revealed significant floristic similarity between the floras of the Maranguape and Baturité massifs, indicating this area as a priority for conservation. The preliminary assessment of conservation status highlights a dramatic scenario for the tribe, with 19 species at some level of threat.